Genetic engineering and trade : panacea or dilemma for developing countries - Nielsen, Chantal Pohl (2001)
Offers a preliminary quantitative assessment of the impact that consumers' changing attitude toward genetic modification might have on world trade patterns, with emphasis on the developing countries. Uses a multiregional computable general equilibrium (CGE) model for this purpose.